2012
DOI: 10.5923/j.env.20120206.02
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Analysis of Groundwater Samples of Bichi Local Government Area of Kano State of Nigeria

Abstract: The physicochemical properties of groundwater from various locations in Bichi Local

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
26
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 12 publications
5
26
1
Order By: Relevance
“…However, chloride concentrations in excess of about 250 mg/l can give rise to detectable taste in water. Chloride levels in the borehole water were above the levels reported by [16], but within the range reported by [2,22,24].…”
supporting
confidence: 73%
See 2 more Smart Citations
“…However, chloride concentrations in excess of about 250 mg/l can give rise to detectable taste in water. Chloride levels in the borehole water were above the levels reported by [16], but within the range reported by [2,22,24].…”
supporting
confidence: 73%
“…The quality of groundwater is affected by the characteristics of the media through which the water passes on its way to the groundwater zone of saturation [15][16]. The greater part of the soluble constituents in ground water comes from soluble minerals in soils and sedimentary rocks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [19], colour in drinking water is usually due to the presence of colour organic matter associated with the humus fraction of soil or the presence of iron and other metals, either as natural impurities or as corrosion products. From results obtained, it was observed that, the values of suspended solids varies between 30.20-52.30mg/L with higher values at DS and lower at sampling point JM.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of Groundwater depends on various chemical constituent and their concentration which are mostly derived from the geological data of the particular region. Groundwater is generally less susceptible to contamination and pollution when compared to surface water bodies [1].…”
Section: Introductionmentioning
confidence: 99%